The effect of meteoric water on the very fine crystalline dolomite reservoir in the shallow burial zone: A case study of the Ma55 submember of Majiagou Formation in Ordos Basin - Lan, Haoxiang; Guo, Min; Fu, Meiyan; Deng, Hucheng; Gluyas, Jon; Xu, Wang; Tang, Mingyuan; Wu, Dong; Li, Yilin; Guo, Hengwei (Frontiers in Energy Research, 2023)
This study aims to reveal the effect of karstification on the dolostone reservoirs in the shallow burial zone from the Ma55 submember of Majiagou Formation in the Daniudi gas field, Ordos Basin. The karstification has obviously changed the physical properties of dolostone reservoirs in the vertical vadose zone and the horizontal phreatic zone, but its influence on the dolostone reservoirs in the shallow burial zone beneath the phreatic surface is still unclear. The diagenesis and paragenesis of the Ma 55 submember were identified and interpreted through petrological study, combined with data from electron probe, X-ray diffraction analysis and geochemical parameters of diagenetic minerals. The color of the very fine crystalline dolomite under the cathode luminescence is dark red and red. The order degree of dolomite ranges from 0.54 to 0.91, showing the origin of early seepage-reflux dolomitization. There are a large number of different calcite cements as fills within the pores and fractures. The color of the calcite cement under the cathodoluminescence is orange-yellow, with a zonal structure. Hydrothermal fluid during late diagenesis could be identified by the authigenic fluorite filling in the fractures. According to the assembly of diagenetic minerals, the very fine crystalline dolostones have experienced the seepage-reflux dolomitization, meteoric water dissolution, shallow burial cementation and late cementation. The void spaces of the very fine crystalline dolostones are intercrystalline pores and micro-fractures. Although a large number of dissolved pores and caves developed in the period of meteoric water dissolution, these caves and dissolved pores has been mostly filled by multi-stages of cementation. Therefore, the effect of meteoric water on dolostone reservoirs in the shallow burial zone beneath the phreatic surface is not obvious. The main controlling factor for the quality of dolostone reservoir was dolomitization. This study provides a new understanding of the influence of meteoric water on reservoir quality in the shallow burial zone during the paleokarst period.